Advanced Cutting Tool Technology and Machine Processes. - Al-Samarai, Riyadh A. (CRC Press, 2025)
Today's industry heavily relies on advanced cutting tool technology and manufacturing techniques to enhance quality and efficiency in production. This undergraduate-level textbook is dedicated to exploring the latest developments that enhance tool performance, lower costs, and boost productivity. The mission of this textbook is to provide readers with a thorough understanding of cutting-edge technologies and methods used in cutting tools and industrial processes.Advanced Cutting Tool Technology and Machine Processes steps into the world of modern cutting tools used in the metallurgical industry. Each tool is meticulously dissected, showcasing its distinctive features and methods of operation. The text explores advanced metalcutting and processing techniques, including laser, water, and plasma cutting. By covering these cuttingedge methods, students and professionals can remain at the forefront of industry advancements. In addition to detailed tool descriptions, this textbook offers practical guidance on utilizing tools effectively and safely, as well as tips on tool maintenance to ensure longevity and peak performance. To enhance comprehension, this textbook incorporates exercise problems, case studies, and practical examples that illustrate how theoretical knowledge is applied in realworld scenarios. This handson approach aids in the development of problemsolving skills and the practical application of concepts. Lastly, this textbook provides comprehensive information on the properties of various metals and how to handle them effectively. This knowledge is crucial in selecting the appropriate tools for each type of metal, guaranteeing precision and efficiency in cutting processes.This textbook is ideal for undergraduate students in production, materials, industrial, mechatronics, marine, mechanical, and manufacturing engineering programs, and is also useful for graduate programs related to higher-level machining topics, as well as professional engineers and technicians.Figure slides and a solutions manual for available for qualified textbook adoptions.